ANALISIS USAHA HOME INDUSTRI KERUPUK RAMBAK - Aini, Syarifah; Fatmawati, Erlin Widya (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
The purpose of this research is to know the amount of cost, acceptance, profit, profitability, and R / C Ratio from home industry crackers rambak in Sembon Village Satreyan District Kanigoro Blitar District. The result of this research shows that the total variable cost at rambak cracker agroindustry center is equal to Total variable cost Rp 1,139,783, - per day, total fixed cost Rp 4,953, - per day. So the total total cost of production is Rp 1,144,076, - per month. The breakeven point or BEP unit is 3 units. BEP Rp for RP 16,017, -. BEP revenue of Rp 16,017, - per day. Received revenue of Rp 1.650.000, - so the profit earned by employers is amounted to Rp 505,924, -. While the profitability of business is 44% which means this business is profitable. Home industry that run during this efficiency has been shown with R / C ratio of more than 1 that is equal to 1.44. Based on the criteria used, this business has been efficient because the efficiency value of more than 1. This means that every Rp 1.00 issued by the entrepreneur at the beginning of the business activities will get 1.44 times revenue from the cost incurred at the end of the business activity. This can be interpreted that home industry crackers rambak said Eligible to run. From this research it is suggested that entrepreneurs do creations by adding a sense of the product, so that the quality of the product can be increased and not less competitive with similar entrepreneurs from other regions. For the government, the Government of Blitar Regency through the Department of Industry and Trade and other related agencies should try to help develop the business crackers rambak by providing low-interest capital loans to entrepreneurs agro-industry crackers rambak.